2019
DOI: 10.13075/mp.5893.00805
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of the circulatory system to stress and electromagnetic fields emitted by mobile phones – 24-h monitoring of ECG and blood pressure

Abstract: StreszczenieWstęp: W badaniach eksperymentalnych zaobserwowano wpływ korzystania z telefonu komórkowego na pracę serca, m.in. wydłużenie odstępu QTc oraz zmiany w wartościach ciśnienia tętniczego. Także stres może wywoływać zmiany w układzie krążenia. Brak jednak badań uwzględniających jednoczesne oddziaływanie stresu i pola elektromagnetycznego (PEM). Oba czynniki dotyczą m.in. pracowników sieci komórkowych. Materiał i metody: Spośród 208 badanych we wcześniejszych etapach metodą ankietową 55 osób wyraziło zg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…In [9] Szyjkowska et al confirmed that work-related stress is strongly correlated with the heart rate and blood pressure; work-related stress in men was usually in association with higher blood pressure, whereas more prominent heart rate variability was usually observed in women. Moreover, stress also affects cognitive abilities; people suffering from stress make more mistakes and perform tasks less accurately [1].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In [9] Szyjkowska et al confirmed that work-related stress is strongly correlated with the heart rate and blood pressure; work-related stress in men was usually in association with higher blood pressure, whereas more prominent heart rate variability was usually observed in women. Moreover, stress also affects cognitive abilities; people suffering from stress make more mistakes and perform tasks less accurately [1].…”
Section: Discussionmentioning
confidence: 96%
“…Among many different physiological stress indicators, such as blood pressure, cortisol level, increased skin conductivity, and head and body movements, HRV is considered one of the reliable methods for assessing the physiological response of the body in response to stress. HRV is caused by the interaction of the sympathetic and parasympathetic parts of the autonomic nervous system and can be analyzed in time and frequency domains [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Длительность разговора с использованием мобильных телефонов также отражается на состоянии сердечно-сосудистой системы. В экспериментальном исследовании A. Szyjkowska et al [14] показано, что общение человека по мобильному телефону более 60 мин в сутки существенным образом сказывается на показателях артериального давления и достоверно (p = 0,04) отличается от показателей, полученных у людей, пользующихся телефоном менее часа в день. Выявленные нами корреляционные связи показателей первичной заболеваемости болезнями, характеризующимися повышенным кровяным давлением, и СЭЭ подтверждают эти данные.…”
unclassified